2015
DOI: 10.5999/aps.2015.42.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Breast Lipofilling: A Review of Current Practice

Abstract: Lipofilling is a reconstructive and aesthetic technique that has recently grown in popularity and is increasingly being used in breast surgery. Previous concerns had been raised regarding its safety when used for remodelling and reconstruction of the breast; however, these concerns have since been dismissed. Over the subsequent two decades, little evidence has been found to support these early theoretical concerns, and growing numbers of proponents of the procedure are confident in its safety. Many development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…The persistent clinical confusion associated with the viability and predictability of fat grafting is related to the mechanism of fat survival in the recipient area (Zhu et al 2010). For large-volume fat transfers or relocations into a hostile recipient bed, the beneficiary area vascularity might be insufficient for the ischemic graft, leading to graft necrosis (Sinno et al 2016;Kasem et al 2015). This may be particularly true for injections into areas where the circulation and wound-healing capacity is impaired by previous fibrosis due to surgery, injections, radiotherapy, or any other acquired pathology (Kasem et al 2015;Yoshimura et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The persistent clinical confusion associated with the viability and predictability of fat grafting is related to the mechanism of fat survival in the recipient area (Zhu et al 2010). For large-volume fat transfers or relocations into a hostile recipient bed, the beneficiary area vascularity might be insufficient for the ischemic graft, leading to graft necrosis (Sinno et al 2016;Kasem et al 2015). This may be particularly true for injections into areas where the circulation and wound-healing capacity is impaired by previous fibrosis due to surgery, injections, radiotherapy, or any other acquired pathology (Kasem et al 2015;Yoshimura et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For large-volume fat transfers or relocations into a hostile recipient bed, the beneficiary area vascularity might be insufficient for the ischemic graft, leading to graft necrosis (Sinno et al 2016;Kasem et al 2015). This may be particularly true for injections into areas where the circulation and wound-healing capacity is impaired by previous fibrosis due to surgery, injections, radiotherapy, or any other acquired pathology (Kasem et al 2015;Yoshimura et al 2006). One recent innovation to deal with such problems is the enrichment of the transplant with autologous regenerative cells (Yoshimura et al 2010;Yoshimura et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coleman technique was superior to conventional liposuction for harvesting and processing fat grafts because the Coleman fat grafts have a greater number of viable adipocytes and sustain more optimal cellular function than fat grafts harvested with conventional liposuction performed by an experienced surgeon [7]. Approximately the same time, a growing body of literature emerged suggesting that other procedures performed on the breast, such as reduction mammoplasties, also lead to scarring that is visible during breast screening and is far in excess of what would be expected after lipofilling [15], [16], [17]. Subsequent studies showed that these artefacts did not appreciably affect screening [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately the same time, a growing body of literature emerged suggesting that other procedures performed on the breast, such as reduction mammoplasties, also lead to scarring that is visible during breast screening and is far in excess of what would be expected after lipofilling [15], [16], [17]. Subsequent studies showed that these artefacts did not appreciably affect screening [17], [18]. In addition, several case reports and case series published over the years have not provided any definitive evidence to support these and other concerns about AFG.…”
Section: Introductionmentioning
confidence: 99%